Prospective, Randomized, Comparative Study of the Cutaneous Effects of a Topical Body Treatment Compared to a Bland Moisturizer. (2nd April 2021) - Carruthers, Jean; Bourne, Gyasi; Bell, Michaela; Widgerow, Alan
Abstract: Background: Over time human skin thins and loses elasticity; topical treatments attempt to reverse this process. Objectives: The aim of this study was to assess the efficacy of TransFORM Body Treatment (TFB) in skin rejuvenation compared to a bland moisturizer on the extensor and volar forearms. Methods: Blinded participants were given 2 products to apply on the designated forearms with follow-up at 4, 8, and 12 weeks. Measurements included skin thickness, photography, dermatopathology, cutaneous elasticity determined by 2 different methods, and patient-reported outcomes. All were compared to baseline. Results: Changes between bland moisturizer and TFB were recorded for the following parameters. (1) Roughness: extensor –0.09 mm for bland moisturizer and –0.26 mm for TFB ( P = 0.174); volar 0.01 mm for bland moisturizer and –0.23 mm for TFB ( P = 0.004). (2) Recoil velocity: volar –56°/sec for bland moisturizer and –24°/sec for TFB ( P = 0.61); extensor –95°/sec for bland moisturizer and –63°/sec for TFB ( P = 0.57). Retraction speed: volar –3.25 ms for bland moisturizer and –20.08 ms for TFB ( P = 0.33); extensor –2.17 ms for bland moisturizer and –10.83 ms for TFB ( P = 0.66). Histologically, TFB resulted in an increase in mucopolysaccharide content, new collagen, and number of elastin fibers in the papillary dermis. Changes in the Rao-Goldman score were also observed: volar –0.17 for bland moisturizer and –0.33 for TFB ( P = 0.25); extensor –0.08 for bland moisturizer and –0.17 for TFB ( P = 0.36). Conclusions: Histology showed production of new collagen and elastin. Quantification of changes in skin thickness, skin retraction speed, and skin recoil velocity showed trends that agree with the visual data. Level of Evidence: 4: